Molecular Study of Human Mammary Tumor Virus in Iraqi Women with Breast Cancer - Mohsin, Tamarah y.; Al-Faham, Mohammed A.; Al-Hadithi, Waleed K.; Pogo, Peatriz G. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Earlier reports related the presence of Mouse Mammary Tumor Virus -like gene sequences to human breast carcinoma. Mouse Mammary Tumor Virus -like gene is a retrovirus, namely, a virus containing reverse transcriptase which transcript its RNA to DNA in a process that enables genetic material from the retrovirus to become a part of the genes of an infected cell permanently. The virus that found in women was designated as Human Mammary Tumor Virus by the authors, who have investigated the presence of Human Mammary Tumor Virus sequences in a many human breast tissues and in many countries.Objectives: Detect HMTV genome in Iraqi women of breast cancer.Patients and Methods: Formalin Fixed, Paraffin Embedded Tissues were collected from 50-breast cancer women with their age range (23-82 years) compared to 5 normal breast tissues as a control group.  DNA was extracted from and by Nested PCR, using specific primers for amplifying Envelop gene for HMTV were taken in Jovac Center in Amman/Jordan.Results: There were no detected signals for HMTV in study cases.Conclusions: The absence of HMTV DNA in breast tissues cancers needs a large sample size to correlate HMTV with breast carcinoma.